Chronic Retained Products of Conception Masked by Müllerian Duct Anomaly: The Diagnostic Value of Hysteroscopy - Prashant Suryarao; Komal Chaudhary (Annals of African Medicine, 2026)
Abstract Müllerian duct anomalies are congenital uterine malformations that may present with pelvic pain, menstrual irregularities, or infertility. However, acquired intrauterine pathologies can occasionally mimic congenital anomalies on imaging, leading to diagnostic confusion. We report a rare case of a 24-year-old woman presenting with chronic pelvic pain and 3 months of amenorrhea, in whom pelvic magnetic resonance imaging (MRI) suggested a Müllerian duct anomaly with abnormal uterine vascularity. Notably, MRI demonstrated a hypointense septum-like structure within the uterine cavity, associated with fundal T2 hyperintense lesion and serpentine myometrial flow voids. Contrary to radiological findings, intraoperative diagnostic hysteroscopy revealed cervical adhesions and chronic retained products of conception (RPOC) with fundal intrauterine adhesions, without evidence of any Müllerian duct anomaly. Adhesiolysis and removal of retained tissue restored near-normal uterine cavity anatomy. This case highlights the potential for chronic RPOC to masquerade as congenital uterine anomalies on MRI and emphasizes hysteroscopy as the definitive diagnostic and therapeutic modality when imaging findings are inconclusive or discordant with clinical presentation.